1996
DOI: 10.1002/(sici)1098-2736(199604)33:4<369::aid-tea2>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Spatial abilities of high-school students in the perception of geologic structures

Abstract: The specific spatial abilities required for the study of basic structural geology were characterized by quantitative and qualitative data analysis. A geologic spatial ability test (GeoSAT) was developed and administered to 115 comprehensive high-school students. Six of these students were interviewed. An analysis of students' incorrect answers revealed two types of answers: (a) nonpenetrative answers, which were based on external exposures of the structure; and (b) penetrative answers, which indicated attempts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0
10

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(119 citation statements)
references
References 25 publications
3
106
0
10
Order By: Relevance
“…Research has shown that the ability to visualize and think in two-and three-dimensions is an asset to successfully interpreting many science concepts, especially in earth science (Chadwick, 1978;Kali and Orion, 1996). Spatial ability in all students can be significantly improved by manipulating imagery (Kali, et.al., 1997), as is done with a GIS.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the ability to visualize and think in two-and three-dimensions is an asset to successfully interpreting many science concepts, especially in earth science (Chadwick, 1978;Kali and Orion, 1996). Spatial ability in all students can be significantly improved by manipulating imagery (Kali, et.al., 1997), as is done with a GIS.…”
Section: Discussionmentioning
confidence: 99%
“…W fizyce poziom zdolności do wizualizacji przestrzennej determinuje wykonanie takich zadań fizycznych z kinematyki, jak przewidywanie dwuwymiarowego ruchu obiektów czy rozumienie i interpretacja wykresów kinematycznych oraz różnych układów odniesienia (Kozhevnikov, Motes i Hegarty, 2007). W geografii wyobrażenie sobie transformacji w czasie i w przestrzeni struktur geologicznych wymaga udziału zdolności przestrzennych (Kali i Orion, 1996). Rozumienie map konturowych i topograficznych, map frontów atmosferycznych, zdjęć satelitarnych czy proporcji układu sło-necznego także wiąże się z poziomem zdolności przestrzennych, a zwłaszcza z poziomem zdolności do rotacji mentalnej (Black, 2005).…”
Section: Związek Zdolności Przestrzennych Z Naukami śCisłymiunclassified
“…즉 학생들의 판구조론과 관련된 여러 현상 이해를 위한 구체적 비유물을 활용한 연구 (이지은 외, 2003) 로서 판구조론 개념을 맥락으로 진행된 연구들, 정보 통신기술(ICT)을 활용한 과학 탐구능력 및 정의적 영역의 효과에 관한 연구 (정진우 외, 2004), 판 경계 부에 대한 이해의 유형을 비교한 연구 (박수경, 2009; 정구송, 2009), 판 구조론에 대한 오개념을 분석한 연구 (정경진 외, 2007; 최성철과 안건상, 2008)에 그 치고 있다. 특히 학생들이 직접 경험하지 못하고, 경험적 공간 의 한계를 넘어서는 다양한 개념들, 지구의 내부 구 조, 지질구조, 판의 운동과 판 경계부 등 판구조론에 관련된 개념들의 이해는 공간능력의 발달과 매우 밀 접하게 연관되고 있음이 알려지고 있다 (Black, 2005;Burton and Mattietti, 2011;Pretty and Rule, 2008;Self and Golledge, 1994;Titus and Horsman; (Kali and Orion, 1996), 지하수와 관련된 개 념을 연구하거나 (정진우 외, 2009;Pretty and Rule, 2008), 층서와 시간의 관련 개념을 조사한 연구 (Burton and Mattietti, 2011), 판의 분포와 판의 경계부에 대 한 오개념을 조사한 연구 (정경진 외, 2007 Table 3. Nonpaired t-test of achievement of plates' motion between two different groups …”
Section: 구분하여 두 집단 간의 판의 운동 관련 개념 성취도에 차이가 있는지를 알아보기 위해 T-검정을unclassified